2011
DOI: 10.1108/00035591111097684
|View full text |Cite
|
Sign up to set email alerts
|

Azole derivatives as inhibitors for the corrosion of irradiated and non‐irradiated carbon steel in HNO3 solution

Abstract: PurposeThe purpose of this paper is to investigate the effects of several azole derivatives on the corrosion inhibition of irradiated and non‐irradiated plain carbon steel in 0.5 M nitric acid (HNO3) solutions at 30‐60°C and to study the mechanism of their inhibitive action.Design/methodology/approachThe inhibition efficiency was evaluated by means of weight‐loss determinations and polarization techniques at different temperatures. The type of adsorption isotherm, inhibition efficiency, surface coverage and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…2 (5) where R corr is the rate of corrosion from weight loss, A is Arrhenius constant, R is the gas constant and T is the absolute temperature. Figure 3 represents Arrhenius plot (log R corr vs. 1/T ) for uninhibited and inhibited 1 M HCl containing 1000 ppm of the studied compounds.…”
Section: C/ C Ppmmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (5) where R corr is the rate of corrosion from weight loss, A is Arrhenius constant, R is the gas constant and T is the absolute temperature. Figure 3 represents Arrhenius plot (log R corr vs. 1/T ) for uninhibited and inhibited 1 M HCl containing 1000 ppm of the studied compounds.…”
Section: C/ C Ppmmentioning
confidence: 99%
“…Inhibitors are generally used in these processes to control the metal dissolution. Most well-known acid inhibitors for steel corrosion are organic compounds containing hetero atoms [2][3][4][5][6][7][8][9][10][11][12]. To be effective, an inhibitor must also displace water from the metal surface, interact with anodic or cathodic reaction sites to retard the oxidation and reduction corrosion reaction, and prevent transport ion of water and corrosion active species on the surface [13].…”
Section: Introductionmentioning
confidence: 99%
“…As widely applicable organic corrosion inhibitors, azoles derivatives have various applications in the industries of copper [5][6][7][8] , aluminum [9][10][11] and their alloys with the exposure to corrosive medium. Azoles derivatives can be applied for a wide range of steels [12][13][14] in acidic or alkaline solutions along with chloride ions. Among the group of azole derivatives, Tolyltriazole (TTA, C 7 H 7 N 3 , with a chemical structure given in Figure 1 5 ) is the most widely used corrosion inhibitor for copper and copper alloys, in cooling water systems, because of its low cost and high performance in corrosion inhibition 5,7,[15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss measurements were performed using compounds of the dimensions (3 x 3 x 0.1) cm 3 . For galvanostatic polarization, a cylindrical rod embedded in araldite with exposed surface area of 0.2 cm 2 was used.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The use of inhibitors is one of the most practical methods for protection against corrosion especially in acid solutions to prevent metal dissolution and acid consumption [1]. Most well known acid inhibitors for steel corrosion are organic compounds containing [2][3][4][5][6][7][8][9][10]. It has been observed that most of the organic inhibitors act by adsorption on the metal surface [11].…”
Section: Introductionmentioning
confidence: 99%